The effect of social cognitive theory-based nutrition education via whatsapp on increasing knowledge and behavioral determinants of mothers in Kediri: A quasi-experimental study - Dzakiyyatul Fikrah 'Arifah; Yayuk Farida Baliwati; Ali Khomsan (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2025)
Poor dietary patterns and poor nutritional status increase the risk of morbidity and mortality. Obesity and overweight are major nutritional issues in Kediri. The family environment, particularly the mother's role as a food gatekeeper, is crucial for shaping children's eating habits. This study applies Social Cognitive Theory (SCT), which emphasizes the interaction between individuals, behavior, and the environment. Social media platforms, such as WhatsApp, can be utilized to promote health. This study examined the effect of SCT-based nutrition education via WhatsApp on mothers' knowledge, self-efficacy, self-regulation, family support, and outcome expectations in improving children's dietary intake. A pre-post quasi-experimental design was used with 80 mothers of elementary school children in Kediri City. The intervention group (n=40) received WhatsApp-based nutrition education for 20 days, whereas the control group (n=40) received an e-booklet at the end of the study. Data were analyzed using Spearman’s test, Mann-Whitney test, and Wilcoxon Signed Rank test. The results showed that WhatsApp-based nutrition education significantly improved knowledge (p=0,005) and outcome expectations (p=0,039) in the intervention group, whereas no significant effects were observed on self-efficacy and self-regulation. WhatsApp-based nutrition education effectively increased mothers' knowledge and outcome expectations. Future studies should consider the duration of the intervention, including follow-up assessment, refining educational media, combining educational methods, and considering additional SCT components.